Positive electrode composite material and preparation method thereof, positive plate, battery and electric equipment

By setting a cladding layer containing halogen anions and cations on the core surface of the O3-phase layered oxide, the structural instability caused by defects during the charge and discharge of the O3-phase layered oxide is solved, and higher cyclic stability and rate performance are achieved.

CN119560530APending Publication Date: 2025-03-04BEIJING EASPRING MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411733069.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

As the positive electrode material, O3-phase layered oxides have anion and cation defects during Na+ transmission during charging and discharging, resulting in unstable structure, which is manifested as poor high voltage cycle stability and large loss of charge and discharge specific capacity of high-rate.

Method used

A cladding layer is provided on the core surface of the O3-phase layered oxide. The cladding layer contains halogen anions and cations. The vacancies interact with the O3-phase layered oxide through the vacancies interaction between the halogen anions and cations and fill in the defects, thereby stabilizing the structure and improving conductivity.

Benefits of technology

The structure collapse caused by anion and cation defects in the charge and discharge cycle of O3 phase layered oxides is effectively avoided, and the cycle stability, high rate performance and capacity retention of the battery are improved, and it is suitable for fast charging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560530A_ABST
    Figure CN119560530A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode composite material and a preparation method thereof, a positive plate, a battery and electric equipment, the positive electrode composite material comprises: an inner core, the inner core comprises an O3 phase layered oxide; the coating layer is arranged on at least part of the surface of the inner core, the coating layer comprises halogen anions and cations, and the cations are selected from at least one of aluminum ions, magnesium ions, calcium ions, sodium ions, barium ions, zinc ions, tin ions, iron ions and copper ions. The coating layer arranged on the surface of the inner core contains halogen anions and cations at the same time, so that cation and anion vacancies appearing in the charge and discharge process of the O3-phase layered oxide can be effectively reduced, and a structural framework of the O3-phase layered oxide can be maintained; and the defects of large electrical property loss and poor cycle stability of the battery under high magnification are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of sodium ion batteries, and specifically relates to a positive electrode composite material and a preparation method thereof, a positive electrode sheet, a battery and electrical equipment. Background Art

[0002] With the vigorous development of new energy, the demand for power batteries and energy storage batteries is increasing. However, the uneven distribution of lithium resources and the low content of lithium in lithium batteries limit the widespread application of lithium batteries in the field of energy storage. Sodium resources are evenly distributed in the world, and its content is much higher than that of lithium. In addition, sodium-ion batteries have less impact on the environment during production and recycling. In addition, sodium-ion batteries have excellent performance in safety and low-temperature cycles. Therefore, as a good supplement to lithium batteries, sodium-ion batteries can effectively fill the gap in the demand for secondary batteries in the field of energy storage.

[0003] The positive electrode material is one of the core components of the battery. At present, the positive electrode materials of sodium-ion batteries mainly include polyanions, Prussian blue and layered oxides. Among them, layered oxides have the advantages of stable structure, high charge and discharge specific capacity, and excellent cycle performance. These advantages of layered oxides make them the most promising positive electrode materials for large-scale marketization. However, layered oxides as positive electrode materials currently face problems such as poor high-voltage cycle stability and large specific capacity loss at high-rate charge and discharge. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to propose a new type of positive electrode composite material and its preparation method, positive electrode sheet, battery and electrical equipment for improving the rate performance and cycle stability of sodium ion batteries. The present application is provided with a coating layer on the surface of the inner core containing both halogen anions and cations, which can effectively reduce the cation and anion vacancies that appear in the O3 phase layered oxide during the charge and discharge process, which is beneficial to maintain the structural skeleton of the O3 phase layered oxide, and improve the defects of large loss of electrical performance of the battery at high rates and poor cycle stability.

[0005] In one aspect of the present application, the present application proposes a positive electrode composite material. According to an embodiment of the present application, the positive electrode composite material includes:

[0006] An inner core, the inner core comprising an O3 phase layered oxide;

[0007] The coating layer is arranged on at least a portion of the surface of the inner core, and the coating layer includes halogen anions and cations, and the cations are selected from at least one of aluminum ions, magnesium ions, calcium ions, sodium ions, barium ions, zinc ions, tin ions, iron ions and copper ions.

[0008] According to the positive electrode composite material of the embodiment of the present application, a coating layer is provided on at least part of the surface of the core including the O3 phase layered oxide, and the coating layer includes halogen anions and cations. During the charge and discharge cycle (especially during charge and discharge at a high rate current), the halogen anions in the coating layer can effectively enter the anion vacancies appearing in the O3 phase layered oxide, and the cations in the coating layer can effectively enter the cation vacancies appearing in the O3 phase layered oxide, filling the Na + During the transmission, there are structural vacancies of anions and cations, which can effectively avoid the structural collapse of O3-phase layered oxides caused by anion and cation defects during the charge and discharge cycle, allowing the battery to adapt to larger currents for charge and discharge. At the same time, the halogen anions in the coating layer can also promote Na + Conductivity, improving the conductivity of the positive electrode composite material. In summary, the halogen anions and cations in the coating layer interact with each other, and can jointly stabilize the structure of the positive electrode composite material, so that the positive electrode composite material can maintain structural stability during a long cycle, and can also effectively improve the conductivity of the positive electrode composite material and expand the electrochemical window of the positive electrode composite material. As a result, the cycle stability, high rate performance and capacity retention rate of the battery using the positive electrode composite material of the present application can be effectively improved. And the battery using the positive electrode composite material of the present application can be suitable for fast charging.

[0009] At the same time, the surface of the O3-phase layered oxide is provided with a coating layer, which can effectively isolate the O3-phase layered oxide material from direct contact with the air, greatly improving the stability of the O3-phase layered oxide material in the air. In addition, the coating layer on the surface of the O3-phase layered oxide can also effectively reduce the residual alkali content on the surface of the material. The reduction of the residual alkali content can effectively reduce the gas generation phenomenon of the battery in the subsequent charge and discharge cycles, greatly improving the cycle stability of the battery.

[0010] In addition, the positive electrode composite material according to the above embodiment of the present application may also have the following additional technical features:

[0011] In some embodiments of the present application, the halogen anion is selected from at least one of a fluoride ion, a chloride ion, and a bromide ion.

[0012] In some embodiments of the present application, the mass content of the halogen anions in the positive electrode composite material is 300ppm to 3900ppm, preferably 1500ppm to 3000ppm; and / or, the mass content of the cations in the positive electrode composite material is 300ppm to 3800ppm, preferably 1000ppm to 3000ppm.

[0013] In some embodiments of the present application, the chemical formula of the O3 phase layered oxide is Na xTMO2, wherein 0.9<x≤1.1, TM is selected from at least two of Ni, Fe, Mn, Zn, Ca, Cu, Ti, Al, Sc, Sr, Sn, Zr and Co; and / or, the median particle size D of the positive electrode composite material 50 It is 10 μm to 20 μm, preferably 14 μm to 18 μm.

[0014] In some embodiments of the present application, in the XRD spectrum of the positive electrode composite material, there is a characteristic diffraction peak of the (003) crystal plane at 2θ of 16.600° to 16.700°.

[0015] In some embodiments of the present application, the pH value of the positive electrode composite material is not greater than 12.3.

[0016] In some embodiments of the present application, the residual alkali in the positive electrode composite material includes Na2CO3 and NaOH, the mass content of Na2CO3 in the positive electrode composite material is not more than 0.3%, and the mass content of NaOH in the positive electrode composite material is not more than 1.6%.

[0017] In the second aspect of the present application, the present application proposes a method for preparing the above-mentioned positive electrode composite material, comprising:

[0018] The O3 phase layered oxide precursor is mixed with a sodium source and subjected to a first sintering to obtain an O3 phase layered oxide;

[0019] The O3 phase layered oxide, the halogen anion source and the cation source are mixed and sintered for a second time to obtain a positive electrode composite material.

[0020] According to the method for preparing the above-mentioned positive electrode composite material in an embodiment of the present application, the method forms a coating layer including halogen anions and cations on the surface of the O3 phase layered oxide. During the charge and discharge cycle (especially during the charge and discharge at a high rate current), the halogen anions in the coating layer can effectively enter the anion vacancies appearing in the O3 phase layered oxide, and the cations in the coating layer can effectively enter the cation vacancies appearing in the O3 phase layered oxide, filling the Na + During the transmission, there are structural vacancies of anions and cations, which can effectively avoid the structural collapse of O3-phase layered oxides caused by anion and cation defects during the charge and discharge cycle, allowing the battery to adapt to larger currents for charge and discharge. At the same time, the halogen anions in the coating layer can also promote Na +The conductivity of the positive electrode composite material is improved. In summary, the halogen anions and cations in the coating layer interact with each other to stabilize the structure of the positive electrode composite material, so that the positive electrode composite material can maintain structural stability during long cycles, and can also effectively improve the conductivity of the positive electrode composite material and expand the electrochemical window of the positive electrode composite material. As a result, the cycle stability, high rate performance and capacity retention rate of the battery using the positive electrode composite material of the present application can be effectively improved.

[0021] At the same time, by forming a coating layer on the surface of the O3 phase layered oxide, the method can effectively isolate the O3 phase layered oxide material from direct contact with the air, greatly improving the stability of the O3 phase layered oxide material in the air. In addition, the coating layer on the surface of the O3 phase layered oxide can also effectively reduce the residual alkali content on the surface of the material. The reduction in the residual alkali content can effectively reduce the gas production phenomenon in the subsequent charge and discharge cycles of the battery, greatly improving the cycle stability of the battery. In addition, the preparation method is simple and easy to implement, and is suitable for large-scale preparation of positive electrode composite materials.

[0022] In some embodiments of the present application, the ratio of the molar number of sodium element in the sodium source to the total molar number of all metal elements in the O3 phase layered oxide precursor is 1.01-1.1; and / or, the sodium source includes at least one of sodium nitrate, sodium carbonate, and sodium hydroxide; and / or, the temperature of the first sintering is 800°C-1100°C, preferably 900°C-1000°C; and / or, the cooling rate of the first sintering is 2°C / min-10°C / min, preferably 5°C / min-8°C / min; and / or, the O3 phase layered oxide precursor is mixed with the sodium source using a first high speed mixer, the rotation speed of the first high speed mixer is 200rpm / min-1000rpm / min, and the mixing time is 5min-20min.

[0023] In some embodiments of the present application, the mass of the halogen anions in the halogen anion source is 500ppm to 4000ppm, preferably 1500ppm to 3000ppm, of the O3-phase layered oxide; and / or, the mass of the cations in the cation source is 500ppm to 4000ppm, preferably 1000ppm to 3000ppm, of the O3-phase layered oxide; and / or, the cation source includes at least one of aluminum oxide, magnesium oxide, calcium oxide, sodium oxide, barium oxide, zinc oxide, tin oxide, iron oxide, copper oxide, sodium carbonate, calcium carbonate and barium carbonate; and / or Or, the halogen anion source includes at least one of sodium fluoride, sodium chloride and sodium bromide; and / or, the temperature of the second sintering is 500°C to 850°C, preferably 650°C to 750°C; and / or, the cooling rate of the second sintering is 3°C / min to 10°C / min, preferably 6°C / min to 10°C / min; and / or, a second high-speed mixer is used to mix the O3 phase layered oxide, the halogen anion source and the cation source, the rotation speed of the second high-speed mixer is 400rpm / min to 800rpm / min, and the mixing time is 8min to 18min.

[0024] In the third aspect of the present application, the present application proposes a positive electrode sheet. According to an embodiment of the present application, the positive electrode sheet comprises the positive electrode composite material described in the first aspect of the present application or the positive electrode composite material prepared by the method described in the second aspect of the present application.

[0025] In a fourth aspect of the present application, the present application provides a battery. According to an embodiment of the present application, the battery includes the positive electrode sheet described in the third aspect of the present application.

[0026] In a fifth aspect of the present application, the present application proposes an electric device. According to an embodiment of the present application, the electric device includes the battery described in the fourth aspect of the present application.

[0027] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The precursor Ni of Example 4 of the present application 0.30 Fe 0.31 Mn 0.31 Sr 0.01 Morphology of (OH)2;

[0029] Figure 2 It is the positive electrode material Cu@NaNi of Example 4 of the present application 0.30 Fe 0.31 Mn 0.31 Sr 0.01Morphology of O2@F;

[0030] Figure 3 The positive electrode material NaNi of Comparative Example 2 of this application 0.30 Fe 0.31 Mn 0.31 Sr 0.01 The morphology of O2;

[0031] Figure 4 The positive electrode material Cu@NaNi of Example 4 0.30 Fe 0.31 Mn 0.31 Sr 0.01 O2@F and the positive electrode material NaNi of comparative example 2 0.30 Fe 0.31 Mn 0.31 Sr 0.01 XRD pattern of O2. DETAILED DESCRIPTION

[0032] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.

[0033] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0034] This application is proposed by the inventor based on the following issues:

[0035] O3-phase layered oxides are used as positive electrode materials during the charge and discharge process. + Anion and cation defects (i.e., anion and cation vacancies) will appear during transmission, resulting in an unstable structure of the O3 phase layered oxide, which in turn leads to problems such as poor high-voltage cycle stability and large specific capacity loss at high-rate charge and discharge in the O3 phase layered oxide.

[0036] In view of this, in one aspect of the present application, the present application proposes a positive electrode composite material (K@Na xTMO2@J). According to an embodiment of the present application, the positive electrode composite material comprises: a core, the core comprises an O3 phase layered oxide; a coating layer, the coating layer is arranged on at least a portion of the surface of the core, the coating layer comprises a halogen anion and a cation, and the cation is selected from aluminum ions (Al 3+ ), magnesium ion (Mg 2+ ), calcium ions (Ca 2+ ), sodium ion (Na + ), barium ions (Ba 2+ ), zinc ion (Zn 2+ ), tin ions (Sn 4+ ), iron ions (Fe 3+ ) and copper ions (Cu 2+ ) at least one of. Among them, Na x TMO2 represents an O3 phase layered oxide, K represents a cation, and J represents a halogen anion.

[0037] The following is a detailed description of the principle by which the positive electrode composite material proposed in this application can achieve the above beneficial effects:

[0038] The present invention provides a coating layer on at least part of the surface of the core including the O3 phase layered oxide, wherein the coating layer includes halogen anions and cations. During the charge-discharge cycle (especially during the charge-discharge at a high rate current), the halogen anions in the coating layer can effectively enter the anion vacancies in the O3 phase layered oxide, and the cations in the coating layer can effectively enter the cation vacancies in the O3 phase layered oxide, thereby filling the Na + During the transmission, there are structural vacancies of anions and cations, which can effectively avoid the structural collapse of O3-phase layered oxides caused by anion and cation defects during the charge and discharge cycle, allowing the battery to adapt to larger currents for charge and discharge. At the same time, the halogen anions in the coating layer can also promote Na + Conductivity, improving the conductivity of the positive electrode composite material. In summary, the halogen anions and cations in the coating layer interact with each other, and can jointly stabilize the structure of the positive electrode composite material, so that the positive electrode composite material can maintain structural stability during a long cycle, and can also effectively improve the conductivity of the positive electrode composite material and expand the electrochemical window of the positive electrode composite material. As a result, the cycle stability, high rate performance and capacity retention rate of the battery using the positive electrode composite material of the present application can be effectively improved. And the battery using the positive electrode composite material of the present application can be suitable for fast charging.

[0039] At the same time, the surface of the O3-phase layered oxide is provided with a coating layer, which can effectively isolate the O3-phase layered oxide material from direct contact with the air, greatly improving the stability of the O3-phase layered oxide material in the air. In addition, the coating layer on the surface of the O3-phase layered oxide can also effectively reduce the residual alkali content on the surface of the material. The reduction of the residual alkali content can effectively reduce the gas generation phenomenon of the battery in the subsequent charge and discharge cycles, greatly improving the cycle stability of the battery.

[0040] In addition, the O3-phase layered oxide with a coating layer has a stable layered structure, a large Na interlayer spacing, and a large Na / Me ratio, which can accommodate more Na + , so it has a higher specific capacity.

[0041] It should be noted that if halogen anions are doped into the O3 phase layered oxide (i.e., the halogen anions enter the O3 phase layered oxide lattice), the halogen anions doped in the O3 phase layered oxide lattice cannot replenish the anion vacancies that appear in the O3 phase layered oxide during the charge and discharge cycle; at the same time, the halogen anions doped in the O3 phase layered oxide lattice cannot interact with the cations to jointly stabilize the structure of the positive electrode composite material.

[0042] According to some specific embodiments of the present application, the halogen anion is selected from fluoride ion (F - ), chloride ion (Cl - ) and bromide ion (Br - ), so that the above-mentioned type of halogen anions can further effectively enter the anion vacancies in the O3 phase layered oxide during the charge-discharge cycle, thereby further effectively avoiding the structural collapse of the O3 phase layered oxide due to anion defects during the charge-discharge cycle. At the same time, the above-mentioned type of halogen anions can further promote Na + conduction, further improving the conductivity of the positive electrode composite material.

[0043] According to some further specific embodiments of the present application, the mass content of halogen anions in the positive electrode composite material is 300ppm to 3900ppm, for example, it can be 300ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 3900ppm, etc. By limiting the mass content of halogen anions in the positive electrode composite material to the above range, it can be further ensured that the halogen anions effectively enter the anion vacancies appearing in the O3 phase layered oxide during the charge and discharge cycle, thereby further effectively avoiding the structural collapse of the O3 phase layered oxide due to anion defects during the charge and discharge cycle. At the same time, it can be further ensured that the halogen anions promote Na +The conductivity of the positive electrode composite material is further improved. Preferably, the mass content of the halogen anion in the positive electrode composite material is 1500ppm to 3000ppm.

[0044] The inventors found that if the content of halogen anions is too high, impurities will be formed during the coating process, causing the structure of the layered oxide to be destroyed during the charge and discharge process, thereby reducing the electrochemical performance of the battery; if the content of halogen anions is too low, the coating effect will not be obvious, resulting in no significant improvement in the electrochemical performance of the battery.

[0045] According to some other specific embodiments of the present application, the mass content of cations in the positive electrode composite material is 300ppm to 3800ppm, for example, it can be 300ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 3800ppm, etc. By limiting the mass content of cations in the positive electrode composite material to the above range, it can be further ensured that the cations effectively enter the cation vacancies appearing in the O3 phase layered oxide during the charge and discharge cycle, thereby further effectively avoiding the phenomenon of structural collapse of the O3 phase layered oxide due to cation defects during the charge and discharge cycle. Preferably, the mass content of cations in the positive electrode composite material is 1000ppm to 3000ppm.

[0046] The inventors found that if the cation content is too high, impurities will be formed during the coating process, causing the structure of the layered oxide to be destroyed during the charge and discharge process, thereby reducing the electrochemical performance of the battery; if the cation content is too low, the coating effect will not be obvious, resulting in no significant improvement in the electrochemical performance of the battery.

[0047] According to some other specific embodiments of the present application, the chemical formula of the O3 phase layered oxide is Na x TMO2, wherein 0.9<x≤1.1 (for example, x can be 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.10, etc.), TM is selected from at least two of Ni, Fe, Mn, Zn, Ca, Cu, Ti, Al, Sc, Sr, Sn, Zr and Co. The above-mentioned types of O3 phase layered oxides have high Na content and unstable structure, and generally have problems such as large charge and discharge specific energy loss after rate performance test, poor cycle performance, and easy drop in later charge and discharge specific energy. The present application provides a coating layer including halogen anions and cations on the surface of the O3 phase layered oxide, so that it has a stable layered structure, a large Na interlayer distance, a large Na / Me ratio, and can accommodate more Na + , so it has a higher specific capacity.

[0048] According to some specific embodiments of the present application, the median particle size D of the positive electrode composite material is 50 The particle size is 10 μm to 20 μm (for example, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, etc.), preferably 14 μm to 18 μm. The particle shape is not particularly limited, and the particle shape may be spherical, elliptical, multi-headed or other irregular shapes.

[0049] According to some other specific embodiments of the present application, the median particle size D50 of the inner core of the O3 phase layered oxide is 10 μm to 18 μm (for example, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, etc.), preferably 12 μm to 16 μm.

[0050] According to some further specific embodiments of the present application, in the XRD spectrum of the positive electrode composite material, there is a characteristic diffraction peak of the (003) crystal plane at 2θ of 16.600° to 16.700°.

[0051] According to some other specific embodiments of the present application, the pH value of the positive electrode composite material is not greater than 12.3. It can be seen that the residual alkali content on the surface of the positive electrode composite material is relatively small. The reduction in the residual alkali content can further effectively reduce the gas production of the battery in subsequent charge and discharge cycles, thereby greatly improving the cycle stability of the battery.

[0052] According to some other specific embodiments of the present application, the residual alkali in the positive electrode composite material includes Na2CO3 and NaOH, the mass content of Na2CO3 in the positive electrode composite material is not more than 0.3%, and the mass content of NaOH in the positive electrode composite material is not more than 1.6%, thereby further ensuring that the residual alkali content on the surface of the positive electrode composite material is less, and the reduction in the residual alkali content can further effectively reduce the gas production of the battery in subsequent charge and discharge cycles, thereby further improving the cycle stability of the battery.

[0053] In the second aspect of the present application, the present application proposes a method for preparing the above-mentioned positive electrode composite material. According to the embodiments of the present application, referring to the attached Figure 1 , the method comprising:

[0054] S100: mixing an O3 phase layered oxide precursor with a sodium source and performing a first sintering to obtain an O3 phase layered oxide;

[0055] In this step, an O3 phase layered oxide precursor is mixed with a sodium source, and then the mixed material is placed in an atmosphere furnace for sintering, and compressed air is introduced throughout the process to perform the first sintering to obtain an O3 phase layered oxide.

[0056] In the embodiment of the present application, the O3 phase layered oxide Na formed by the first sintering x TMO2 exists in the form of agglomerates, and the particle form may be spherical, elliptical, multi-headed or other irregular particles. Preferably, the layered oxide Na x The median particle size of TMO2 is D 50 The thickness is 10 μm to 18 μm, preferably 12 μm to 16 μm.

[0057] According to some specific embodiments of the present application, the ratio of the molar number of the sodium element in the sodium source to the total molar number of all metal elements in the O3 phase layered oxide precursor is 1.01 to 1.1 (for example, it can be 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.10, etc.), thereby preparing a chemical formula of Na x O3 phase layered oxide of TMO2, where 0.9<x≤1.1.

[0058] According to some further specific embodiments of the present application, the first high-speed mixer (e.g., high-speed mixer 3-8L) can be used to mix the O3-phase layered oxide precursor with the sodium source, the rotation speed of the first high-speed mixer is 200rpm / min to 1000rpm / min (e.g., 200rpm / min, 300rpm / min, 400rpm / min, 500rpm / min, 600rpm / min, 700rpm / min, 800rpm / min, 900rpm / min, 1000rpm / min, etc.), and the mixing time is 5min to 20min (e.g., 5min, 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min, 14min, 15min, 16min, 17min, 18min, 19min, 20min, etc.). Thus, it can be ensured that the O3-phase layered oxide precursor is fully mixed with the sodium source.

[0059] In the embodiment of the present application, the first sintering can be divided into three processes: a heating stage, a heat preservation stage and a cooling stage. The first is a heating stage, and the heating rate can be 2°C / min to 10°C / min (for example, 2°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc.), and the temperature is increased to 800°C to 1100°C. Then there is a heat preservation stage: the temperature of the heat preservation stage is 800°C to 1100°C (for example, it can be 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, etc.), preferably 900°C to 1000°C, and the heat preservation time is 15h to 25h (for example, it can be 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, 25h, etc.). The last stage is cooling, and the cooling rate can be 2℃ / min~10℃ / min (for example, 2℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min), preferably 5℃ / min~8℃ / min, to room temperature. In this way, it can be ensured that the O3 phase layered oxide precursor reacts fully with the sodium source to obtain a chemical formula of Na x O3 phase layered oxide of TMO2, where 0.9<x≤1.1.

[0060] The inventors found that if the temperature of the first sintering is too high, it will cause over-burning, resulting in the generation of impurity phases (such as NiO), thereby reducing the electrochemical performance of the positive electrode material; if the temperature of the first sintering is too low, the material will not be able to form a layered oxide structure, resulting in changes in the material. The inventors also found that if the cooling rate of the first sintering is too high, the material will have a compact molding structure, thereby reducing the electrochemical performance of the positive electrode material; if the cooling rate of the first sintering is too low, the material will be at high temperature for too long, and related impurities will be generated, thereby reducing the electrochemical performance of the positive electrode material.

[0061] In the embodiments of the present application, the sodium source may be a soluble sodium salt conventionally used in the art, and there is no particular limitation thereto. Preferably, the sodium source is selected from at least one of sodium nitrate, sodium carbonate, and sodium hydroxide.

[0062] According to some further specific embodiments of the present application, the preparation method of the above-mentioned O3 phase layered oxide precursor is as follows:

[0063] In the presence of a solvent, at least two of a manganese source, a nickel source, an iron source, a zinc source, a calcium source, a copper source, a titanium source, an aluminum source, a scandium source, a strontium source, a tin source, a zirconium source, and a cobalt source, a complexing agent, and a precipitant are mixed in a stoichiometric ratio and then subjected to a co-precipitation reaction to obtain an O3 phase layered oxide precursor.

[0064] In the embodiments of the present application, the above-mentioned iron source, manganese source, nickel source, zinc source, calcium source, copper source, titanium source, aluminum source, scandium source, strontium source, tin source, zirconium source, and cobalt source can be soluble iron sources, soluble manganese sources, soluble nickel sources, soluble zinc sources, soluble calcium sources, soluble copper sources, soluble titanium sources, soluble aluminum sources, soluble scandium sources, soluble strontium sources, soluble tin sources, soluble zirconium sources, and soluble cobalt sources conventionally used in the art. There is no particular limitation on this. Preferably, the above-mentioned nickel source, iron source, and manganese source are selected from at least one of sulfates, nitrates, and chlorides containing Ni, Fe, and Mn.

[0065] In the embodiments of the present application, the precipitant may be a precipitant commonly used in the art, and there is no particular limitation thereto. Preferably, the precipitant is at least one of sodium hydroxide and lithium hydroxide. The concentration of the precipitant may be 2 mol / L to 11 mol / L.

[0066] In the embodiments of the present application, the complexing agent can be a complexing agent commonly used in the art, and there is no particular limitation on this. Preferably, the complexing agent is at least one of citric acid, ammonia water, disodium ethylenediaminetetraacetate, and ammonium bicarbonate. The concentration of the complexing agent can be 2 mol / L to 12 mol / L.

[0067] S200: mixing the O3 phase layered oxide, the halogen anion source and the cation source, and performing a second sintering to obtain a positive electrode composite material.

[0068] In this step, the O3 phase layered oxide, the halogen anion source and the cation source are mixed so that the halogen anion source and the cation source coat the O3 phase layered oxide. After the coating is uniform, the coated mixed material is then placed in an atmosphere furnace for sintering, and compressed air is introduced throughout the process for a second sintering to obtain a positive electrode composite material (K@Na x TMO2@J).

[0069] According to some specific embodiments of the present application, a second high mixer (for example, high mixer 3-8L) can be used to mix the O3 phase layered oxide, the halogen anion source and the cation source, the rotation speed of the second high mixer is 400rpm / min to 800rpm / min (for example, it can be 400rpm / min, 500rpm / min, 600rpm / min, 700rpm / min, 800rpm / min, etc.), and the mixing time is 8min to 18min (for example, it can be 8min, 9min, 10min, 11min, 12min, 13min, 14min, 15min, 16min, 17min, 18min, etc.).

[0070] According to some further specific embodiments of the present application, the second sintering can be divided into three processes: a heating stage, a heat preservation stage and a cooling stage. The first is the heating stage, and the heating rate of the heating stage can be 4°C / min to 10°C / min (for example, it can be 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc.), and the temperature is increased to 500°C to 850°C. Then there is the heat preservation stage: the temperature of the heat preservation stage is 500°C to 850°C (for example, it can be 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, etc.), preferably 650°C to 750°C, and the heat preservation time is 8h to 17h (for example, it can be 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, etc.). The last stage is cooling, and the cooling rate is 3℃ / min to 10℃ / min (for example, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 10℃ / min, etc.), preferably 6℃ / min to 10℃ / min. Finally, the temperature is cooled to room temperature to obtain the positive electrode composite material (K@Na x TMO2@J). Thus, it can be ensured that the halogen anion source and the cation source fully react to form a coating layer, which is coated on the surface of the O3 phase layered oxide.

[0071] The inventors found that if the temperature of the second sintering is too high, the coating material will become hard, resulting in the need to increase the crushing power for subsequent crushing, which will easily break the coating layer, resulting in poor coating effect; if the temperature of the second sintering is too low, the coated material will not reach the coating temperature, causing the coated anions and cations to remain in the state before coating and become impurities, thereby reducing the electrochemical performance of the positive electrode material. The inventors also found that if the cooling rate of the second sintering is too high, the coating material will not be able to be coated more tightly, and the formed coating layer will not be dense; if the cooling rate of the second sintering is too low, it will lead to a waste of energy.

[0072] According to some other specific embodiments of the present application, the mass of the halogen anions in the halogen anion source is 500ppm to 4000ppm of the O3 phase layered oxide (for example, it can be 500ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, etc.), thereby ensuring that the mass content of the halogen anions in the formed positive electrode composite material is in the range of 300ppm to 3900ppm, thereby further ensuring that the halogen anions effectively enter the anion vacancies appearing in the O3 phase layered oxide during the charge and discharge cycle, effectively avoiding the phenomenon of structural collapse of the O3 phase layered oxide due to anion defects during the charge and discharge cycle, and at the same time, further ensuring that the halogen anions promote Na+ The conductivity of the positive electrode composite material is further improved. Preferably, the mass of the halogen anions in the halogen anion source is 1500ppm to 3000ppm of the O3-phase layered oxide.

[0073] According to some other specific embodiments of the present application, the mass of the cations in the cation source is 500ppm to 4000ppm of the O3-phase layered oxide (for example, it can be 500ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, etc.), thereby ensuring that the mass content of the halogen cations in the formed positive electrode composite material is within the range of 300ppm to 3800ppm, thereby further ensuring that the cations effectively enter the cation vacancies appearing in the O3-phase layered oxide during the charge and discharge cycle, thereby further effectively avoiding the phenomenon of structural collapse of the O3-phase layered oxide due to cation defects during the charge and discharge cycle. Preferably, the mass of the cations in the cation source is 1000ppm to 3000ppm of the O3-phase layered oxide.

[0074] In the embodiments of the present application, the specific type of the above-mentioned cation source is not particularly limited. As some preferred embodiments, the cation source includes at least one of aluminum oxide, magnesium oxide, calcium oxide, sodium oxide, barium oxide, zinc oxide, tin oxide, iron oxide, copper oxide, sodium carbonate, calcium carbonate and barium carbonate.

[0075] In the embodiments of the present application, the specific type of the above-mentioned halogen anion source is not particularly limited. As some preferred embodiments, the halogen anion source includes at least one of sodium fluoride, sodium chloride and sodium bromide.

[0076] According to the method for preparing the above-mentioned positive electrode composite material in an embodiment of the present application, the method forms a coating layer including halogen anions and cations on the surface of the O3 phase layered oxide. During the charge and discharge cycle (especially during charge and discharge at a high rate current), the halogen anions in the coating layer can effectively enter the anion vacancies appearing in the O3 phase layered oxide, and the cations in the coating layer can effectively enter the cation vacancies appearing in the O3 phase layered oxide, filling the Na + During the transmission, there are structural vacancies of anions and cations, which can effectively avoid the structural collapse of O3-phase layered oxides caused by anion and cation defects during the charge and discharge cycle, allowing the battery to adapt to larger currents for charge and discharge. At the same time, the halogen anions in the coating layer can also promote Na +The conductivity of the positive electrode composite material is improved. In summary, the halogen anions and cations in the coating layer interact with each other to stabilize the structure of the positive electrode composite material, so that the positive electrode composite material can maintain structural stability during long cycles, and can also effectively improve the conductivity of the positive electrode composite material and expand the electrochemical window of the positive electrode composite material. As a result, the cycle stability, high rate performance and capacity retention rate of the battery using the positive electrode composite material of the present application can be effectively improved.

[0077] At the same time, the method can effectively isolate the O3 phase layered oxide material from direct contact with the air by forming a coating layer on the surface of the O3 phase layered oxide, greatly improving the stability of the O3 phase layered oxide material in the air. In addition, the coating layer on the surface of the O3 phase layered oxide can also effectively reduce the residual alkali content on the surface of the material. The reduction in the residual alkali content can effectively reduce the gas generation phenomenon of the battery in subsequent charge and discharge cycles, greatly improving the cycle stability of the battery.

[0078] In addition, the preparation method is simple and easy to implement, and is suitable for large-scale preparation of positive electrode composite materials.

[0079] In the third aspect of the present application, the present application proposes a positive electrode sheet. According to an embodiment of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, and the positive electrode active material layer includes the positive electrode composite material of the first aspect of the present application, or the positive electrode composite material prepared by the method of the second aspect. It should be noted that the features and advantages described above for the positive electrode composite material and its preparation method are also applicable to the positive electrode sheet, and will not be repeated here.

[0080] According to an embodiment of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, and the positive electrode active material layer includes the above-mentioned positive electrode composite material, a positive electrode binder and a positive electrode conductive agent. In an embodiment of the present application, the positive electrode current collector can be made of a material with good conductivity and mechanical strength, preferably aluminum foil.

[0081] In the embodiments of the present application, the specific type of the positive electrode conductive agent is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific examples, the positive electrode conductive agent includes at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. Similarly, the specific type of the positive electrode binder is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific examples, the positive electrode binder includes at least one of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).

[0082] According to some embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the positive electrode sheet, such as the positive electrode composite material, the positive electrode conductive agent, the positive electrode binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0083] In the fourth aspect of the present application, the present application proposes a battery. According to an embodiment of the present application, the battery includes the positive electrode sheet of the third aspect. Thus, the cycle stability, high rate performance and capacity retention rate of the battery can be effectively improved, and the battery can be suitable for fast charging. In an embodiment of the present application, the above-mentioned battery can be a sodium ion battery.

[0084] Specifically, the battery comprises the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte of the third aspect, and the separator is arranged between the positive electrode sheet and the negative electrode sheet. The specific material of the separator is not particularly limited. As some specific examples, the separator comprises at least one of a PP separator, a PE separator, a single-sided ceramic separator, a double-sided ceramic separator, a non-woven separator and a glass fiber separator.

[0085] In the embodiments of the present application, the electrolyte includes electrolyte salt and organic solvent, wherein the specific types and compositions of the electrolyte salt and organic solvent are conventional choices in the battery field and can be selected according to actual needs.

[0086] In some embodiments, the electrolyte salt may include, but is not limited to, at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium bis(trifluoromethanesulfonyl)imide (NaN(CF3SO2)2), sodium bis(fluorosulfonyl)imide (NaN(SO2F)2), sodium bis(oxalatoborate) (NaB(C2O4)2), and sodium difluorooxalatoborate (NaBF2C2O4).

[0087] In some embodiments, the organic solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), fluoroethylene carbonate (FEC), diethylene glycol dimethyl ether (DEGDME), ethylene glycol dimethyl ether (DME), 1,3-dioxolane (DOL), and tetraethylene glycol dimethyl ether (TEGDME).

[0088] The battery of the present application may include a battery cell form, a battery module form and a battery pack form. In some embodiments, the battery cells can be assembled into a battery module, and the number of battery cells contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module. In some embodiments, the battery modules can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.

[0089] It should be noted that the above-described features and advantages for the positive electrode are also applicable to the battery and will not be described in detail here.

[0090] In a fifth aspect of the present application, the present application proposes an electric device. According to an embodiment of the present application, the electric device includes the above-mentioned battery. The features and advantages described above for the battery are also applicable to the electric device and will not be repeated here.

[0091] Specifically, the electrical equipment may be, but is not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, etc. Electric toys may include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft may include airplanes, rockets, space shuttles, and spacecraft, etc.

[0092] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0093] Example 1

[0094] This embodiment provides a positive electrode composite material, and the preparation method thereof includes:

[0095] (1) Ni 0.30 Fe 0.31 Mn 0.31 Zn 0.01 The (OH)2 precursor and sodium carbonate were placed in a high-speed mixer at a speed of 800 rpm / min at a molar ratio of 1:1.02, and mixed for 15 minutes to make them fully mixed; the mixed powder was placed in an oxygen atmosphere furnace, heated to 900°C at a heating rate of 5°C / min, high-temperature solid-phase sintering for 20 hours, and then cooled to room temperature at a cooling rate of 5°C / min to obtain a layered oxide material Na 1.02 Ni 0.30 Fe 0.31Mn 0.31 Zn 0.01 O2 is a black powder.

[0096] (2) The layered oxide material Na 1.02 Ni 0.30 Fe 0.31 Mn 0.31 Zn 0.01 The black powder of O2 was mixed with NaF and CaCO3 in a high-speed mixer at 500 rpm / min for 12 minutes to fully coat the powder. The mass of F ions in NaF was 2000 ppm of the mass of the layered oxide material, and the mass of Ca ions in CaCO3 was 2000 ppm of the mass of the layered oxide material. The coated powder was placed in an air atmosphere furnace, heated to 650°C at a heating rate of 6°C / min, sintered for 10 hours, and then cooled to room temperature at a cooling rate of 6°C / min to obtain the positive electrode composite material Ca@Na 1.02 Ni 0.30 Fe 0.31 Mn 0.31 Zn 0.01 O2@F.

[0097] Example 2

[0098] This embodiment provides a positive electrode composite material, and the preparation method thereof includes:

[0099] (1) Ni 0.31 Fe 0.33 Mn 0.33 Zn 0.005 The (OH)2 precursor and sodium nitrate were placed in a high-speed mixer at a speed of 900 rpm / min at a molar ratio of 1:1.04, and mixed for 20 minutes to make them fully mixed; the mixed powder was placed in an oxygen atmosphere furnace, heated to 1000°C at a heating rate of 6°C / min, high-temperature solid-phase sintering for 25 hours, and then cooled to room temperature at a cooling rate of 8°C / min to obtain a layered oxide material Na 1.04 Ni 0.31 Fe 0.33 Mn 0.33 Zn 0.005 O2 is a black powder.

[0100] (2) Layered oxide material Na 1.04 Ni 0.30 Fe 0.31 Mn 0.31 Zn 0.005The black powder of O2 was mixed with NaCl and Al2O3 in a high-speed mixer at 600 rpm / min for 15 minutes to fully coat the material. The mass of Cl ions in NaCl was 1000 ppm of the mass of the layered oxide material, and the mass of Al ions in Al2O3 was 500 ppm of the mass of the layered oxide material. The coated powder was placed in an air atmosphere furnace, heated to 700°C at a heating rate of 5°C / min, sintered for 12 hours, and then cooled to room temperature at a cooling rate of 5°C / min to obtain the positive electrode composite material Al@Na 1.04 Ni 0.30 Fe 0.31 Mn 0.31 Zn 0.005 O2@Cl.

[0101] Example 3

[0102] This embodiment provides a positive electrode composite material, and the preparation method thereof includes:

[0103] (1) Ni 0.30 Fe 0.31 Mn 0.31 Mg 0.1 The (OH)2 precursor and sodium hydroxide were placed in a high-speed mixer at a speed of 1000 rpm / min at a molar ratio of 1:1.06, and mixed for 10 minutes to make them fully mixed; the mixed powder was placed in an oxygen atmosphere furnace, heated to 1050°C at a heating rate of 4°C / min, high-temperature solid-phase sintering for 16 hours, and then cooled to room temperature at a cooling rate of 4°C / min to obtain a layered oxide material Na 1.06 Ni 0.30 Fe 0.31 Mn 0.31 Mg 0.1 O2 is a black powder.

[0104] (2) Layered oxide material Na 1.06 Ni 0.30 Fe 0.31 Mn 0.31 Mg 0.1 The black powder of O2 was mixed with NaBr and CaCO3 in a high-speed mixer at 700 rpm / min for 18 minutes to fully coat the powder. The mass of Br ions in NaBr was 3000 ppm of the mass of the layered oxide material, and the mass of Ca ions in CaCO3 was 3000 ppm of the mass of the layered oxide material. The coated powder was placed in an air atmosphere furnace, heated to 700°C at a heating rate of 10°C / min, sintered for 12 hours, and then cooled to room temperature at a cooling rate of 10°C / min to obtain the positive electrode composite material Ca@Na 1.06 Ni 0.30 Fe0.31 Mn 0.31 Mg 0.1 O2@Br.

[0105] Example 4

[0106] This embodiment provides a positive electrode composite material, and the preparation method thereof includes:

[0107] (1) Ni 0.30 Fe 0.31 Mn 0.31 Sr 0.01 The (OH)2 precursor and sodium hydroxide were placed in a high-speed mixer at a speed of 900 rpm / min at a molar ratio of 1:1.08, and mixed for 18 minutes to make them fully mixed; the mixed powder was placed in an oxygen atmosphere furnace, heated to 950°C at a heating rate of 7°C / min, high-temperature solid-phase sintering for 19 hours, and then cooled to room temperature at a cooling rate of 7°C / min to obtain a layered oxide material Na 1.08 Ni 0.30 Fe 0.31 Mn 0.31 Sr 0.01 O2 is a black powder.

[0108] (3) Layered oxide material Na 1.08 Ni 0.30 Fe 0.31 Mn 0.31 Sr 0.01 The black powder of O2 was mixed with NaF and CuO in a high-speed mixer at 800 rpm / min for 13 minutes to fully coat the powder. The mass of F ions in NaF was 2500 ppm of the mass of the layered oxide material, and the mass of Cu ions in CuO was 2500 ppm of the mass of the layered oxide material. The coated powder was placed in an air atmosphere furnace, heated to 750°C at a heating rate of 4°C / min, sintered for 14 hours, and then cooled to room temperature at a cooling rate of 4°C / min to obtain the positive electrode composite material Cu@Na 1.08 Ni 0.30 Fe 0.31 Mn 0.31 Sr 0.01 O2@F.

[0109] Example 5

[0110] This embodiment provides a positive electrode composite material, and the preparation method thereof includes:

[0111] (1) Ni 0.33 Fe 0.33 Mn 0.33The (OH)2 precursor and sodium hydroxide were placed in a high-speed mixer at a speed of 1000 rpm / min at a molar ratio of 1:1.10, and mixed for 16 minutes to make them fully mixed; the mixed powder was placed in an oxygen atmosphere furnace, heated to 1000°C at a heating rate of 9°C / min, high-temperature solid-phase sintering for 22 hours, and then cooled to room temperature at a cooling rate of 9°C / min to obtain a layered oxide material Na 1.1 Ni 0.33 Fe 0.33 Mn 0.33 O2 is a black powder.

[0112] (2) Layered oxide material Na 1.1 Ni 0.33 Fe 0.33 Mn 0.33 The black powder of O2 was mixed with NaCl and SnO2 in a high-speed mixer at 700 rpm / min for 17 minutes to fully coat the powder. The mass of Cl ions in NaCl was 3000 ppm of the mass of the layered oxide material, and the mass of Sn ions in SnO2 was 3000 ppm of the mass of the layered oxide material. The coated powder was placed in an air atmosphere furnace, heated to 750°C at a heating rate of 7°C / min, sintered for 17 hours, and then cooled to room temperature at a cooling rate of 7°C / min to obtain the positive electrode composite material Sn@Na 1.1 Ni 0.33 Fe 0.33 Mn 0.33 O2@Cl.

[0113] Embodiments 6 to 22

[0114] The preparation methods of this embodiment are basically the same as those of embodiment 1, and the differences are shown in Table 1.

[0115] Table 1

[0116]

[0117]

[0118] Comparative Example 1

[0119] The preparation method of this comparative example is basically the same as that of Example 1, except that:

[0120] (2) The layered oxide material Na 1.02 Ni 0.30 Fe 0.31 Mn 0.31 Zn 0.01The black powder of O2 was placed in an air atmosphere furnace, heated to 650℃ at a heating rate of 6℃ / min, sintered for 10h, and then cooled to room temperature at a cooling rate of 6℃ / min to obtain the layered oxide material Na 1.02 Ni 0.30 Fe 0.31 Mn 0.31 Zn 0.01 O2.

[0121] Comparative Example 2

[0122] The preparation method of this comparative example is basically the same as that of Example 4, except that:

[0123] (2) The layered oxide material Na 1.08 Ni 0.30 Fe 0.31 Mn 0.31 Sr 0.01 The black powder of O2 was placed in an atmosphere furnace, heated to 750℃ at a rate of 4℃ / min, sintered for 14h, and then cooled to room temperature at a rate of 4℃ / min to obtain the layered oxide material Na 1.08 Ni 0.30 Fe 0.31 Mn 0.31 Sr 0.01 O2.

[0124] Comparative Example 3

[0125] The preparation method of this comparative example is basically the same as that of Example 1, except that:

[0126] (2) The layered oxide material Na 1.02 Ni 0.30 Fe 0.31 Mn 0.31 Zn 0.01 The black powder of O2 was mixed with CaCO3 in a high-speed mixer at 500 rpm / min for 12 minutes to fully coat the powder, wherein the mass of Ca ions in CaCO3 was 2000 ppm of the mass of the layered oxide material. The coated powder was placed in an air atmosphere furnace, heated to 650°C at a heating rate of 6°C / min, sintered for 10 hours, and then cooled to room temperature at a cooling rate of 6°C / min to obtain the positive electrode composite material Ca@Na 1.02 Ni 0.30 Fe 0.31 Mn 0.31 Zn 0.01 O2.

[0127] Comparative Example 4

[0128] The preparation method of this comparative example is basically the same as that of Example 1, except that:

[0129] (2) The layered oxide material Na 1.02 Ni 0.30 Fe 0.31 Mn 0.31 Zn 0.01 The black powder of O2 was mixed with NaF in a high-speed mixer at 500 rpm / min for 12 minutes to fully coat the powder, wherein the mass of F ions in NaF was 2000 ppm of the mass of the layered oxide material. The coated powder was placed in an air atmosphere furnace, heated to 650°C at a heating rate of 6°C / min, sintered for 10 hours, and then cooled to room temperature at a cooling rate of 6°C / min to obtain the positive electrode composite material Na 1.02 Ni 0.30 Fe 0.31 Mn 0.31 Zn 0.01 O2@F.

[0130] Comparative Example 5

[0131] This comparative example provides a method for preparing a positive electrode composite material, which comprises doping halogen anions into an O3 phase layered oxide material, and comprising the following steps:

[0132] (1) Ni 0.30 Fe 0.31 Mn 0.31 Zn 0.01 The (OH)2 precursor and sodium carbonate were mixed at a ratio of 1:1.02, and 0.02 mol of sodium fluoride was placed in a high-speed mixer at a speed of 800 rpm / min and mixed for 15 minutes to make them fully mixed; the mixed powder was placed in an atmosphere furnace, heated to 1000°C at a heating rate of 5°C / min, and sintered at high temperature for 20 hours, and then cooled to room temperature at a cooling rate of 5°C / min to obtain a layered oxide material Na 1.04 Ni 0.30 Fe 0.31 Mn 0.31 Zn 0.01 O2F 0.02 of black powder.

[0133] (2) The layered oxide material Na 1.04 Ni 0.30 Fe 0.31 Mn 0.31 Zn 0.01 O2F 0.02The black powder was mixed with CaCO3 in a high-speed mixer at 500 rpm / min for 12 minutes to fully coat the powder, wherein the mass of Ca ions in CaCO3 was 2000 ppm of the mass of the layered oxide material. The coated powder was placed in an atmosphere furnace, heated to 600°C at a heating rate of 6°C / min, sintered for 10 hours, and then cooled to room temperature at a cooling rate of 6°C / min to obtain the positive electrode composite material Ca@Na 1.04 Ni 0.30 Fe 0.31 Mn 0.31 Zn 0.01 O2F 0.02 .

[0134] Test example:

[0135] The positive electrode materials of Examples 1 to 22 and Comparative Examples 1 to 5 were subjected to ICP test, morphology test, particle size test, XRD test, total alkali test and electrochemical performance test, respectively.

[0136] ICP test: The instrument used is PE Optima 7000DV, and the test conditions are that 5g of sample is completely dissolved in a mixed acid solution of 3mL HNO3+9mL HCl and diluted to 250mL for testing.

[0137] Morphology test: The morphology of the material was observed by scanning electron microscopy (SEM), and the instrument used was a S-4800 scanning electron microscope produced by Hitachi, Japan.

[0138] Particle size test: measured using Malvern Particle Sizer 3000.

[0139] XRD test: The instrument used was an X-ray diffractometer (Rigaku, Smart Lab 9KW), and the test conditions were: the X-ray source was Cu Kα rays, the scanning range was 10°-80°, the scanning rate was 1° / min, and the scanning step was 0.02°.

[0140] Total alkali test: Use Swiss Metrohm potentiometric titrator to perform acid-base titration to test the total alkali content (residual alkali content) in the material.

[0141] Electrochemical performance test: The electrochemical performance of the positive electrode material was tested using an R2025 button-type sodium ion battery.

[0142] The preparation process of sodium ion battery is as follows:

[0143] Preparation of pole pieces: The sodium ion battery positive electrode material, conductive agent SuperP and polyvinylidene fluoride (PVDF) are mixed with an appropriate amount of N-methylpyrrolidone (NMP) in a mass ratio of 95:2.5:2.5 to form a uniform slurry. The slurry is coated on aluminum foil and dried at 120°C for 12 hours. It is then stamped into a positive electrode piece with a diameter of 12 mm and a thickness of 120 μm using a pressure of 100 MPa.

[0144] Battery assembly: In an argon-filled glove box with a water content and oxygen content of less than 5ppm, the positive electrode, separator, negative electrode and electrolyte were assembled into a R2025 button-type sodium-ion battery and left to stand for 6 hours. The negative electrode used a metal sodium sheet with a diameter of 14mm and a thickness of 1mm; the separator used a 25μm thick rubber-coated separator; the electrolyte used a mixture of 1mol / L NaPF6, ethyl methyl carbonate (EMC) and propylene carbonate (PC) in a ratio of 4:6.

[0145] Electrochemical performance test: Shenzhen Xinwell Battery Test System (CT3008) was used to test the electrochemical performance of R2025 button-type sodium-ion batteries. The first charge and discharge capacity test conditions were 0.1C@2-4.0V, 25℃ constant voltage cutoff current was 0.02C; the cycle performance test conditions were 1.0C@2-4.0V25℃. In addition, button-type sodium-ion batteries were tested at constant current at 0.1C, 1C, 5C, and 10C to evaluate the charge and discharge capacity, cycle performance, and volume energy density of different rates of sodium-ion battery cathode materials. During the rate performance test, the higher the ratio of 10C / 0.1C from the high rate charge and discharge capacity, the better the material structure performance is, and it is suitable for fast charge and discharge scenarios. The process from low rate to high rate and then back to low rate proves that the material structure is stable. The higher the capacity retention rate during the cycle, the higher the material stability and the better the battery system cycle performance.

[0146] 1)ICP test:

[0147] The compositions of the positive electrode materials of Examples 1 to 22 and Comparative Examples 1 to 5 were tested by ICP, and the contents of related elements after coating were tested. The results are shown in Table 2.

[0148] Table 2

[0149]

[0150]

[0151] The compositions of the positive electrode materials of Examples 1 to 22 and Comparative Examples 1 to 5 were tested by ICP, and the contents of related elements after coating were tested. The results are shown in Table 2.

[0152] 2) Morphology test:

[0153] The precursor Ni of Example 4 was 0.30 Fe 0.31 Mn 0.31 Sr 0.01 (OH)2 and cathode composite material Cu@NaNi 0.30 Fe 0.31 Mn 0.31 Sr 0.01 O2@F and the positive electrode material NaNi of comparative example 2 0.30 Fe 0.31 Mn 0.31 Sr 0.01 O2 was tested for morphology, and the results were as follows Figure 1 , Figure 2 and Figure 3 As shown. Among them, Figure 1 and Figure 2 The precursor Ni of Example 4 is respectively 0.30 Fe 0.31 Mn 0.31 Sr 0.01 (OH)2 and cathode material Cu@NaNi 0.30 Fe 0.31 Mn 0.31 Sr 0.01 Morphology of O2@F. Figure 3 The positive electrode material NaNi of Comparative Example 2 0.30 Fe 0.31 Mn 0.31 Sr 0.01 Morphology of O2.

[0154] from Figure 1 It can be seen that the precursor Ni of Example 4 0.30 Fe 0.31 Mn 0.31 Sr 0.01 (OH)2 particles are large and round, with smooth surface. Figure 2 It can be seen that the positive electrode material Cu@NaNi of Example 4 0.30 Fe 0.31 Mn 0.31 Sr 0.01 There are relevant black marks on the surface of O2@F, which are the coating materials on the surface of layered oxide materials; Figure 3 It can be seen that the layered oxide material NaNi 0.30 Fe 0.31 Mn 0.31 Sr 0.01 There are no associated black marks on the O2 surface.

[0155] 3) Particle size test:

[0156] The particle sizes of the positive electrode materials of Examples 1 to 22 and Comparative Examples 1 to 5 were tested using a Malvern Particle Sizer 3000. The particle sizes of the positive electrode materials coated in the examples and the particle sizes of the positive electrode materials of the comparative examples were tested. The results are shown in Table 3.

[0157] Table 3

[0158]

[0159]

[0160] It can be seen from Table 3 that the D 50 , D 90 and D 100 The particle size is significantly larger than that of the comparative example 1. 50 , D 90 and D 100 The particle size of Example 4 50 , D 90 and D 100 The particle size is significantly larger than that of D2 in the comparative example 50 , D 90 and D 100 The particle size of the positive electrode composite material A(K@Na x TMO2@J) can increase the particle size after coating.

[0161] 4) XRD test:

[0162] XRD tests were performed on the positive electrode materials of Examples 1-22 and Comparative Examples 1-5, and the results are shown in Table 4. The positive electrode material Cu@NaNi of Example 4 is also provided. 0.30 Fe 0.31 Mn 0.31 Sr 0.01 O2@F and the positive electrode material NaNi of comparative example 2 0.30 Fe 0.31 Mn 0.31 Sr 0.01 The XRD patterns of O2 are shown in the following table. Figure 4 shown.

[0163] Table 4

[0164]

[0165]

[0166] It can be seen from Table 4 that the 2θ of the 003 peak of Examples 1, 6 to 22 is greater than the 2θ of the 003 peak of Comparative Example 1, and the 2θ of the 003 peak of Example 4 is greater than the 2θ of the 003 peak of Comparative Example 2. Therefore, it can be inferred that the positive electrode material (K@Na x The 2θ of the 003 peak of TMO2@J is higher than that of the uncoated cathode material Na x TMO2 is bigger.

[0167] 5) Total alkali test:

[0168] The total alkali test was performed on the positive electrode materials of Examples 1-22 and Comparative Examples 1-5 respectively, so as to compare the changes in the total alkali of the positive electrode materials before and after coating. The results are shown in Table 5.

[0169] Table 5

[0170]

[0171]

[0172] It can be seen from Table 5 that the positive electrode materials (K@Na x TMO2@J) is higher than the uncoated positive electrode material Na of Comparative Example 1-2. x The total alkali content of TMO2 in Na2CO3 (%) and NaOH (%) is significantly reduced. x TMO2@J) has a coating layer that isolates the material from direct contact with the air, greatly improving the stability of the material in the air.

[0173] It can also be seen from Table 5 that compared with Comparative Example 5, the total alkali content and pH of the positive electrode material of Example 1 are further reduced. It can be seen that compared with doping the halogen anions in the O3 phase layered oxide (that is, the halogen anions enter the O3 phase layered oxide lattice), the embodiment of the present application co-coats the halogen anions and cations on the surface of the O3 phase layered oxide lattice, which can further reduce the total alkali content and pH of the positive electrode material.

[0174] 6) Electrochemical performance test:

[0175] The electrochemical properties of the sodium ion battery positive electrode materials prepared in Examples 1-22 and Comparative Examples 1-5 were tested, including the rate performance of the 0.1C first discharge capacity, 1C discharge capacity, 5C discharge capacity, 10C discharge capacity, and the capacity retention rate after 80 cycles at a current of 1C, the capacity retention rate after 200 cycles, and the capacity retention rate after 400 cycles. The specific test results are shown in Tables 6 and 7.

[0176] Table 6

[0177]

[0178]

[0179] Table 7

[0180]

[0181]

[0182] It can be found from Table 6 that the high rate performance of Examples 1-22 is significantly improved compared with Comparative Example 1. x The first discharge specific capacity of TMO2@J is higher than that of the uncoated positive electrode material Na and the positive electrode material Na only coated with anions or cations. x TMO2. With the 1C, 5C, and 10C discharge capacity differences becoming more and more obvious. From this, it can be judged that the positive electrode material (K@Na x TMO2@J) is superior to the uncoated and anion- or cation-coated cathode materials Na in terms of high rate performance. x Therefore, double coating of anions and cations helps to improve the rate performance of the positive electrode material, especially the high rate performance.

[0183] It can also be found from Table 6 that, compared with Example 6 and Example 11, the high-rate performance of Example 1 and Examples 7 to 10 is better. It can be seen that by limiting the mass of halogen anions in the halogen anion source to within the range of 500ppm to 4000ppm of the O3 phase layered oxide, the high-rate performance of the battery is better. At the same time, it can be found that by limiting the mass of halogen anions in the halogen anion source to within the range of 1500ppm to 3000ppm of the O3 phase layered oxide, the high-rate performance of the battery is even better.

[0184] It can also be found from Table 6 that, compared with Example 12 and Example 17, the high-rate performance of Example 1 and Examples 13 to 16 is better. It can be seen that by limiting the mass of cations in the cation source to within the range of 500ppm to 4000ppm of the O3 phase layered oxide, the high-rate performance of the battery is better. At the same time, it can be found that by limiting the mass of cations in the cation source to within the range of 1500ppm to 3000ppm of the O3 phase layered oxide, the high-rate performance of the battery is even better.

[0185] It can also be found from Table 6 that compared with Example 18 and Example 20, the high-rate performance of Example 1 and Example 19 is better. It can be seen that when the temperature of the second sintering is limited to the range of 650°C-750°C, the high-rate performance of the battery is better.

[0186] It can also be found from Table 6 that compared with Comparative Example 5, the high-rate performance of Example 1 is better. It can be seen that compared with doping the halogen anions in the O3 phase layered oxide (that is, the halogen anions enter the O3 phase layered oxide lattice), the embodiment of the present application co-coats the halogen anions and cations on the surface of the O3 phase layered oxide lattice, which can further improve the structural stability of the positive electrode composite material, thereby further improving the high-rate performance of the battery.

[0187] It can be found from Table 7 that the cycle performance of Examples 1-22 is significantly improved compared with Comparative Example 1. x The cycling performance of TMO2@J is better than that of the uncoated cathode material Na and the cathode material Na only coated with anions or cations. x TMO2. With the increase of cycle times, the cycle retention rate of the coated positive electrode material (K@Na x TMO2@J) decreases slowly, while the positive electrode material Na that is not coated and only anion or cation coated x The capacity retention rate of TMO2 is significantly reduced, and even drops. It can be judged that the positive electrode material (K@Na x TMO2@J) has better cycling performance than the uncoated and anion- or cation-coated cathode materials Na x Cyclic performance of TMO2. Therefore, double coating of anions and cations helps to improve the cycling performance of the positive electrode material.

[0188] It can also be found from Table 7 that, compared with Example 6 and Example 11, the cycle performance of Example 1 and Examples 7 to 10 is better. It can be seen that by limiting the mass of halogen anions in the halogen anion source to within the range of 500ppm to 4000ppm of the O3 phase layered oxide, the cycle performance of the battery is better. At the same time, it can be found that by limiting the mass of halogen anions in the halogen anion source to within the range of 1500ppm to 3000ppm of the O3 phase layered oxide, the cycle performance of the battery is even better.

[0189] It can also be found from Table 7 that, compared with Example 12 and Example 17, the cycle performance of Example 1 and Examples 13 to 16 is better. It can be seen that by limiting the mass of cations in the cation source to within the range of 500ppm to 4000ppm of the O3 phase layered oxide, the cycle performance of the battery is better. At the same time, it can be found that by limiting the mass of cations in the cation source to within the range of 1500ppm to 3000ppm of the O3 phase layered oxide, the cycle performance of the battery is even better.

[0190] It can also be found from Table 7 that compared with Example 18 and Example 20, the cycle performance of Example 1 and Example 19 is better. It can be seen that when the temperature of the second sintering is limited to the range of 650°C-750°C, the cycle performance of the battery is better.

[0191] It can also be found from Table 7 that compared with Comparative Example 5, the cycle performance of Example 1 is better. It can be seen that compared with doping the halogen anions in the O3 phase layered oxide (that is, the halogen anions enter the O3 phase layered oxide lattice), the embodiment of the present application co-coats the halogen anions and cations on the surface of the O3 phase layered oxide lattice, which can further improve the structural stability of the positive electrode composite material, thereby further improving the cycle performance of the battery.

[0192] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0193] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A positive electrode composite material, characterized in that: include: An inner core, the inner core comprising an O3 phase layered oxide; The coating layer is arranged on at least a portion of the surface of the inner core, and the coating layer includes halogen anions and cations, and the cations are selected from at least one of aluminum ions, magnesium ions, calcium ions, sodium ions, barium ions, zinc ions, tin ions, iron ions and copper ions.

2. The positive electrode composite material according to claim 1, characterized in that: The halogen anion is selected from at least one of fluoride ion, chloride ion and bromide ion.

3. The positive electrode composite material according to claim 1, characterized in that: The mass content of the halogen anion in the positive electrode composite material is 300ppm to 3900ppm, preferably 1500ppm to 3000ppm; And / or, the mass content of the cation in the positive electrode composite material is 300 ppm to 3800 ppm, preferably 1000 ppm to 3000 ppm.

4. The positive electrode composite material according to any one of claims 1 to 3, characterized in that The chemical formula of the O3 phase layered oxide is Na x TMO2, wherein 0.9<x≤1.1, TM is selected from at least two of Ni, Fe, Mn, Zn, Ca, Cu, Ti, Al, Sc, Sr, Sn, Zr and Co; And / or, the median particle size D of the positive electrode composite material 50 It is 10 μm to 20 μm, preferably 14 μm to 18 μm.

5. The cathode composite material according to any one of claims 1 to 3, characterized in that In the XRD spectrum of the positive electrode composite material, there is a characteristic diffraction peak of the (003) crystal plane at 2θ of 16.600° to 16.700°.

6. The cathode composite material according to any one of claims 1 to 3, characterized in that The pH value of the positive electrode composite material is not greater than 12.

3.

7. The positive electrode composite material according to claim 6, characterized in that: The residual alkali in the positive electrode composite material includes Na2CO3 and NaOH, the mass content of the Na2CO3 in the positive electrode composite material is not more than 0.3%, and the mass content of the NaOH in the positive electrode composite material is not more than 1.6%.

8. A method for preparing the cathode composite material according to any one of claims 1 to 7, characterized in that: include: The O3 phase layered oxide precursor is mixed with a sodium source and subjected to a first sintering to obtain an O3 phase layered oxide; The O3 phase layered oxide, the halogen anion source and the cation source are mixed and sintered for a second time to obtain a positive electrode composite material.

9. The method according to claim 8, characterized in that The ratio of the molar number of the sodium element in the sodium source to the total molar number of all metal elements in the O3 phase layered oxide precursor is 1.01 to 1.1; And / or, the sodium source includes at least one of sodium nitrate, sodium carbonate and sodium hydroxide; And / or, the temperature of the first sintering is 800°C to 1100°C, preferably 900°C to 1000°C; And / or, the cooling rate of the first sintering is 2°C / min to 10°C / min, preferably 5°C / min to 8°C / min; And / or, the O3 phase layered oxide precursor is mixed with the sodium source using a first high speed mixer, the rotation speed of the first high speed mixer is 200 rpm / min to 1000 rpm / min, and the mixing time is 5 min to 20 min.

10. The method according to claim 8 or 9, characterized in that: The mass of the halogen anions in the halogen anion source is 500ppm to 4000ppm, preferably 1500ppm to 3000ppm, of the O3 phase layered oxide; and / or, the mass of the cations in the cation source is 500ppm to 4000ppm, preferably 1000ppm to 3000ppm, of the O3-phase layered oxide; and / or, the cation source comprises at least one of aluminum oxide, magnesium oxide, calcium oxide, sodium oxide, barium oxide, zinc oxide, tin oxide, iron oxide, copper oxide, sodium carbonate, calcium carbonate and barium carbonate; And / or, the halogen anion source comprises at least one of sodium fluoride, sodium chloride and sodium bromide; And / or, the temperature of the second sintering is 500°C to 850°C, preferably 650°C to 750°C; And / or, the cooling rate of the second sintering is 3°C / min to 10°C / min, preferably 6°C / min to 10°C / min; And / or, the O3 phase layered oxide, the halogen anion source and the cation source are mixed using a second high speed mixer, the rotation speed of the second high speed mixer is 400 rpm / min to 800 rpm / min, and the mixing time is 8 min to 18 min.

11. A positive electrode sheet, characterized in that: The invention comprises the positive electrode composite material according to any one of claims 1 to 7 or the positive electrode composite material prepared by the method according to any one of claims 8 to 10.

12. A battery, characterized in that: Including the positive electrode sheet as claimed in claim 11.

13. An electrical equipment, characterized in that: Comprising the battery of claim 12.